Left pulmonary aplasia with multiloculated effusion and pericardial defects in a young adult: a case report - Dantis, Klein; Thippanahalli Ganga, Ranganath; Sahu, Dibakar (Pneumologie, 2022)
Pulmonary aplasia is a rare developmental lung anomaly with unknown etiology. Multiloculated effusion and pericardial defects are even less common with no cases reported up until now. Here, we report the first case of an unusual presentation of a 25-year-old female with recurrent cough for four months, who was diagnosed with left pulmonary aplasia with multiloculated effusion and partial pericardial defects, and who underwent uniportal thoracoscopic drainage and pleurectomy.
Keywords: Lungenaplasie; Entwicklungsanomalie der Lunge; mehrfach gekammerter Erguss; uniportale Thorakoskopie; Perikarddefekte